Optimization of coag-flocculation processes of a newly synthesized quaternized oil palm empty fruit bunch cellulose by response surface methodology toward drinking water treatment process application - Mohtar, S. S. (Springer Verlag, 2017)
An optimization of coagulation and flocculation of kaolin suspension by a newly synthesized quaternized oil palm empty fruit bunch cellulose denoted as a 9QC was investigated using the central composite design of the response surface methodology. The influences of coag-flocculant dosage, pH, and kaolin suspension on turbidity removal efficiency and sludge volume index responses were studied and assessed according to a 23full factorial design. The developed quadratic models revealed that the overall optimum values to obtain the highest performance of the responses were 62.5ï¿½mg/L of coag-flocculant dosage, pH 7, and 1400ï¿½mg/L of kaolin concentration. The predicted optimum responses were found to be in close proximity to the observed responses. The coag-flocculating of river water using 9QC carried out at the optimum values showed encouraging results as compared to alum which is commonly used in drinking water treatment process.